2021
DOI: 10.3390/drones5040142
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Geographical Scale and Multiple Environmental Factors to Delineate the Breeding Distribution of Sea Turtles

Abstract: Temperature is often used to infer how climate influences wildlife distributions; yet, other parameters also contribute, separately and combined, with effects varying across geographical scales. Here, we used an unoccupied aircraft system to explore how environmental parameters affect the regional distribution of the terrestrial and marine breeding habitats of threatened loggerhead sea turtles (Caretta caretta). Surveys spanned four years and ~620 km coastline of western Greece, encompassing low (<10 nests/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 102 publications
1
10
0
Order By: Relevance
“…Our study showed that the distribution of sea turtles at both sites shifted in relation to wind, supporting existing studies in this study region (Schofield et al, 2007;Schofield et al, 2009;Dickson et al, 2021). Wind impacts sea turtles in different ways depending on life stage and habitat.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our study showed that the distribution of sea turtles at both sites shifted in relation to wind, supporting existing studies in this study region (Schofield et al, 2007;Schofield et al, 2009;Dickson et al, 2021). Wind impacts sea turtles in different ways depending on life stage and habitat.…”
Section: Discussionsupporting
confidence: 89%
“…We showed that even one UAS survey at the peak of the breeding season could capture the overall home range of breeding sea turtles, with 50% KUDs for single-surveys similar to that generated from remote tracking datasets (Schofield et al, 2013). Furthermore, by timing surveys to coincide with peak periods of breeding area use (Limpus et al, 2003;Whiting et al, 2013), UASs could be used to conduct scoping surveys to detect habitat use inside and outside of aggregations (Dickson et al, 2021). However, as UASs only capture the distribution of wildlife within surveyed areas, combining them with other approaches, such as remote tracking of individuals (Hart and Hyrenbach, 2009;Wilmers et al, 2015), could be used to validate survey area selection and establish connectivity across surveyed sites.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations